Biochemical characterization, GC-MS metabolite profiling, and heavy metals assessment of Rokshi: safety assessment and nutritional potential of a traditional fermented rice beverage of Monpa tribe - Rosamund Jyrwa; Ananta Choudhury; Andian Ari Anggraeni (Creative Pharma Assent, 2026)
Background: Rokshi is a traditional fermented rice beverage widely consumed by the Monpa tribe of Arunachal Pradesh, a Northeastern State in India, with cultural, nutritional, and biochemical significance. Methodology: Standard analytical methods were employed to determine pH, alcohol content, total acidity, viscosity, and antioxidant properties. Microbial count was assessed using the plate count method. Metabolite profiling and heavy metals analysis were conducted using GC-MS and ICP-OES, respectively. Results and Discussion: Rokshi were reported to be acidic and rich in metabolically important compounds. One-month-old Rokshi beverage showed increased alcohol content (7.54% v/v) as compared to fresh Rokshi beverage (2.59% v/v), with a pH of 4.10 (fresh), which decreased to 3.09 during storage. Total acidity increased from 0.58% to 0.78% after one month of storage. Total flavonoid and phenolic content were 0.205 mg QE/mL and 0.928 mg GAE/mL, respectively, with moderate antioxidant activity. Microbial load decreased in the starter culture (2.15 log CFU/mL) to 0.55 log CFU/mL in the final product. GC-MS analysis identified 28 metabolites, predominantly amino acids, sugars, organic acids, and alcohol. Heavy metals (Cd, Pb, Cr, Mn, Fe, Zn, Ni) were also detected, within the maximum permissible limit, and TTHQ values (<1) indicated no significant non-carcinogenic risk at 250 mL/day consumption. Conclusion: The current study showed that Rokshi holds promise for its nutritional and biochemical properties and has moderate antioxidant potential. The presence of a few biogenic amines and trace contaminants emphasizes the need for purification and further toxicological validation to ensure consumer safety and promote nutraceutical applications for commercial use as a functional fermented beverage.